Regulatory mechanism of ghrelin on testosterone secretion in type 1 diabetic rats - Chien-Chen Lu; Chia-Hsin Chang; Jou-Chun Chou; Po-Ling Yu; Paulus S Wang (Reproduction and Fertility, 2025)
Ghrelin, which is a hormone composed of 28 amino acids that is mainly produced in the stomach, is also secreted by Leydig cells in the testes of rats and humans. The hypothalamus regulates testosterone secretion by releasing gonadotropin-releasing hormone (GnRH), which stimulates the pituitary gland to release luteinizing hormone (LH). LH then prompts the testes to produce testosterone via the activity of steroidogenic acute regulatory protein (StAR). Consequently, ghrelin may play a regulatory role in gonadal function. Male Sprague–Dawley rats were randomly assigned to four groups: the control, ghrelin-treated, diabetic, and diabetic plus ghrelin treatment groups. After the rats were sacrificed, plasma samples were collected. Leydig cells were isolated and cultured with human chorionic gonadotropin (hCG, which is similar to LH and is used to stimulate Leydig cells to synthesize testosterone), 8-bromoadenosine 3′,5′-cyclic monophosphate (8-Br-cAMP, which is an activator of cyclic adenosine monophosphate-dependent protein kinase), or forskolin (an activator of adenylyl cyclase in a wide variety of cell types). Compared with normal treatment, ghrelin treatment in diabetic rats markedly increased plasma testosterone levels by 3.75-fold (P < 0.05), Leydig cell testosterone secretion by 2.8-fold (P < 0.05), GnRH-mediated LH release from the anterior pituitary by 2.95-fold (P < 0.05), and StAR expression by 1.96-fold (P < 0.05) in testicular Leydig cells. These findings indicated that ghrelin enhanced testosterone production in diabetic rats, which was partially achieved by the hypothalamic–pituitary–gonadal axis and StAR. This study emphasized the potential use of ghrelin as a treatment for improving testosterone levels and gonadal function in individuals with diabetes.